Music Intervention Can Improve Emotion in Cancer Patients during Disease Progression - Lei Jia; Jianping Chen; Rainbow Th Ho; Jin Yu; Li Guo; li Li (Archives of Depression and Anxiety - Peertechz Publications, 2016)
Music has long been regarded to aid health and loss-adaptation, but effect of music intervention on  cancer patients is not well-understood. The aims of this study are to summarize and describe the role of music before and after diagnosis. This review examines music intervention studies with randomized designs for patients with cancer published between 1991 and 2015 from three English- language  databases and Chinese-language  databases. Ten  studies  that  met  specific  inclusion criteria were reviewed. Our review indicates that music intervention may have beneficial effects on emotion (anxiety/depression) in patients with cancer. More research is needed to ascertain the most optimal  intervention  methodology on which  cancer  populations  or  which  treatment  modalities are appropriate for such an intervention.